SISTEM PENDUKUNG KEPUTUSAN PEMBERIAN BEASISWA UANG KULIAH TUNGGAL (UKT) MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) DAN TECHNIQUE FOR OTHERS REFERENCE BY SIMILARITY (TOPSIS) - Doharma, Rouli; Parulian, L Taufik; Taufik, Ahmad (Infotech: Journal of Technology Information, 2024)
One viewpoint of the welfare of understudy administrations given by Higher Instruction Teach in an exertion to assist ease the burden of understudy instruction costs is by giving single educational cost grants (UKT) given by the government through instructive educate. In deciding the grant of this grant, there are criteria that must be met by understudies and there's a determination made by the understudy division in deciding which understudies will get this UKT grant. The problems faced in allowing grants are regularly not appropriate on target and it takes very a long time, since they have not utilized a strategy in deciding grant receipts, other than that there are numerous criteria that must be met by the government and higher instruction gets to be an deterrent in choice making. The strategy utilized in this inquire about is the strategy of Expository Chain of command Prepare (AHP) and Method for Others Reference by Closeness to Perfect Arrangement (TOPSIS). The comes about of this think about are anticipated to be able to create a Choice Back Framework show for UKT grant beneficiaries can decide the weight of the criteria and the positioning of grant beneficiaries. ABSTRAKSalah satu aspek kesejahteraan pelayanan kemahasiswaan yang diberikan oleh perguruan tinggi untuk mengurangi beban biaya pendidikan bagi mahasiswa adalah dengan pemberian Beasiswa Belajar Perorangan (UKT) yang diberikan pemerintah melalui lembaga pendidikan. Dalam memutuskan pemberian beasiswa ini, mahasiswa harus memenuhi kriteria tertentu dan Bagian Kemahasiswaan akan melakukan proses seleksi untuk menentukan mahasiswa mana yang akan menerima Beasiswa UKT ini. Permasalahan pemberian beasiswa seringkali tidak efektif dan memakan waktu yang sangat lama. Sebab, tidak ada cara untuk memutuskan penerimaan beasiswa dan banyaknya kriteria  yang ditetapkan pemerintah yang harus dipenuhi, sehingga pendidikan tinggi menjadi kendala dalam pengambilan keputusan. Metode penelitian ini menggunakan metode Analytic Hierarchy Process (AHP) dan Technique for Others Reference by Similarity to Ideal Solution (TOPSIS). Hasil penelitian adalah mengembangkan  model sistem pendukung keputusan untuk menentukan bobot kriteria dan peringkat penerima hibah.